Fellowship as social-pedagogical treatment - Mogens Jensen (Scottish Journal of Residential Child Care)
There is a need for a concept of social-pedagogical treatment as part of the professional terminology of social pedagogy in order to characterise and qualify the professional work going on besides therapeutic or educational sessions. A social-pedagogical concept of treatment is based on communities and their formation, and it is distinct from both the psychological and the medical concept of treatment. The article discusses a residential centre for young people as a social-pedagogical community for its residents and personnel due to their contracts, recognition, and competencies, and maintains that social-pedagogical treatment is a specific and relevant professional term in social work.